Experimental Study of Rainfall Infiltration in an Analog Fracture-matrix System - Zhen Zhong; Huicai Gao; Yunjin Hu (Advances in Materials Science and Engineering)
In this study, an experimental apparatus was developed to investigate unsaturated infiltration in an analog fracture-matrix system. Fracture and adjacent matrix is simulated by sands with various particle sizes. Four rainfall infiltration experiments were performed on the analog fracture-matrix system at a constant rainfall rate of 100 mm/h. The process of rainfall infiltration is measured by a combination method of tensiometers and quick moisture apparatus. The measured results reveal that fracture-matrix interactions certainly exert influences on the hydraulic behaviour of unsaturated fractured matrix, and the fluid flow mainly infiltrates along the nonuniform paths within the matrix. Moreover, it is observed that the influences are greater when using a coarser sand to mimic the fracture. Specifically, the wetting phase in the matrix moves faster than that in the fracture; the fracture, therefore, acts as a vertical capillary barrier, but there exists lateral water exchange from the matrix to the fracture. Overall, this study has demonstrated the importance of fracture/matrix interactions, which should be considered when dealing with unsaturated flow through permeable matrices.